Effects of gender-affirming hormone therapy on gray matter density, microstructure and monoamine oxidase A levels in transgender subjects - Handschuh, PA; Reed, MB; Murgaš, M; Vraka, C; Kaufmann, U; Nics, L; Klöbl, M; Ozenil, M; Konadu, ME; Patronas, EM; Spurny-Dworak, B; Hahn, A; et al. (NeuroImage (Orlando, Fla.), 2024)
•Gender-affirming hormone therapy led to significant changes in gray matter density and microstructure in various brain regions.•Gray matter changes found after gender-affirming hormone therapy were not reflected by monoamine oxidase a density changes in the brain.•Masculinizing gender-affirming hormone therapy resulted in increased sexual desire in transgender men. MAO-A catalyzes the oxidative degradation of monoamines and is thus implicated in sex-specific neuroplastic processes that influence gray matter (GM) density (GMD) and microstructure (GMM). Given the exact monitoring of plasma hormone levels and sex steroid intake, transgender individuals undergoing gender-affirming hormone therapy (GHT) represent a valuable cohort to potentially investigate sex steroid-induced changes of GM and concomitant MAO-A density. Here, we investigated the effects of GHT over a median time period of 4.5 months on GMD and GMM as well as MAO-A distribution volume. To this end, 20 cisgender women, 11 cisgender men, 20 transgender women and 10 transgender men underwent two MRI scans in a longitudinal design. PET scans using [11C]harmine were performed before each MRI session in a subset of 35 individuals. GM changes determined by diffusion weighted imaging (DWI) metrics for GMM and voxel based morphometry (VBM) for GMD were estimated using repeated measures ANOVA. Regions showing significant changes of both GMM and GMD were used for the subsequent analysis of MAO-A density. These involved the fusiform gyrus, rolandic operculum, inferior occipital cortex, middle and anterior cingulum, bilateral insula, cerebellum and the lingual gyrus (post-hoc tests: pFWE+Bonferroni < 0.025). In terms of MAO-A distribution volume, no significant effects were found. Additionally, the sexual desire inventory (SDI) was applied to assess GHT-induced changes in sexual desire, showing an increase of SDI scores among transgender men. Changes in the GMD of the bilateral insula showed a moderate correlation to SDI scores (rho = - 0.62, pBonferroni = 0.047). The present results are indicative of a reliable influence of gender-affirming hormone therapy on 1) GMD and GMM following an interregional pattern and 2) sexual desire specifically among transgender men.